Emerging trends in the use and adoption of E‐participation around the world. Issue 1 (2015) - Hagen, Loni; Kropczynski, Jess; Dumas, Catherine; Lee, Jisue; Vasquez, Fatima Espinoza; Rorissa, Abebe
ABSTRACT: This panel showcases analyses of emerging trends of e‐participation—use of information communication technologies (ICTs) and social media for political participation. E‐participation has gained popularity in many countries, and some cases have shown that e‐participation has actually brought significant changes in societies. In this panel, we address two issues: (1) the impacts of e‐participation on society, and (2) the role of information science in understanding this phenomenon. We will focus on introducing emerging trends in e‐participation and their impact on individuals and societies in South Korea, the United States, and Honduras. Further, we introduce methods for efficiently analyzing e‐participation data, and discuss challenges involved in implementing these methodologies. Because this is intended to be an interactive panel, the audience will be encouraged to engage in discussions and contributing their own experiences and ideas related to current trends in e‐participation in various countries. SPONSORSHIP: SIG III, SIG IEP